A bone paradigm challenging the standard model of myeloma oncogenesis. (April 2022) - Capp, Jean-Pascal; Bataille, Régis
Abstract: The standard model of multiple myeloma (MM) oncogenesis from monoclonal gammopathy of undetermined significance (MGUS) relies on genetic instability in the normal counterparts of MM cells. However, the importance of both MGUS-associated and MM-induced bone changes has been recently re-appraised, emphasizing the bone microenvironment (BME) as a tissue of significance. In this review, we propose that early BME alterations (bone senescence and inflammation, i.e., bone inflamm'aging) at the pre-MGUS stage could be causal, and not simply permissive, and creative of phenotypic instability and genetic alterations thanks to the concept of tissue disruption-induced cell stochasticity (TiDiS). This article offers a bone scenario challenging the chromosome-and-gene-centric standard model of MM oncogenesis. The high incidence of both MGUS and MM in Gaucher disease supports such a scenario. Graphical Abstract: ga1 Highlights: Multiple myeloma (MM) is generally considered as a purely genetics-driven disease. However alterations in the bone microenvironment (BME) intervene early by creating a permissive environment. We consider the potential initiating role of the disruption of the endosteal niche. Early BME alterations could be causal and creative of phenotypic instability and genetic alterations. Bone senescence and inflamm'aging could be at the origin of this early disruption.